Ways of Being: Hittite Empire and Its Borderlands in Late Bronze Age Anatolia and Northern Syria - Durusu-Tanrıöver, Muge (Studia Orientalia Electronica, 2021)
In this paper, I take identity as a characteristic of empire in its periphery, denoting the totality of: 1) the imperial strategies an empire pursues in different regions, 2) the index of empire in each region, and 3) local responses to imperialism. My case study is the Hittite Empire, which dominated parts of what is now modern Turkey and northern Syria between the seventeenth and twelfth centuries BCE, and its borderlands. To investigate the identities of the Hittite imperial system, I explore the totality of the second millennium BCE in two regions. First, I explore imperial dynamics and responses in the Ilgın Plain in inner southwestern Turkey through a study of the material collected by the Yalburt Yaylası Archaeological Landscape Research Project since 2010. Second, I explore the identity of the Hittite Empire in the city of Emar in northern Syria by a thorough study of the textual and archaeological material unearthed by the Emar Expedition. In both cases, I argue that the manifestations of the Hittite Empire were mainly conditioned by the pre-Hittite trajectories of these regions. The strategies that the administration chose to use in different borderlands sought to identify what was important locally, with the Hittite Empire integrating itself into networks that were already established as manifestations of power, instead of replacing them with new ones.